Digital marketing strategies to enhance the competitiveness of MSMEs - lia, laila tanzi (Maliki Interdisciplinary Journal, 2026)
The development of digital technology has brought significant changes to marketing strategies, including within the Micro, Small, and Medium Enterprises (MSMEs) sector in Indonesia. Marketing activities that were previously carried out conventionally are now beginning to shift toward digital media such as social media, marketplaces, and various other online platforms. This research aims to analyze the role of digital marketing in enhancing the competitiveness of MSMEs amid the growth of modern business practices. The research method employed is qualitative with a literature study approach through the examination of academic journals and other reliable sources. The research findings reveal that digital marketing is able to help MSMEs reach a broader market, simplify the product promotion process, and increase the effectiveness of communication with consumers. Besides contributing to higher sales performance, MSMEs also have a crucial role in supporting the national economy through the creation of employment opportunities. However, the implementation of digitalization still encounters several challenges, such as the limited digital capabilities of business actors and constraints in human resources. Therefore, a proper digital strategy is required so that MSMEs can continue to develop and remain able to compete sustainably.